Relationship between cardiovascular health status and attitudes towards responsibility for health - Raevschi, Elena; Grib, Liviu; Penina, Olga; Obreja, Galina (Folia Medica, 2022)
Abstract Introduction : Current concerns of medical scientific research show an increasing interest in the field of individual and community level health promotion based on health responsibility approaches. Achieving and maintaining cardiovascular health of individuals has a significant impact on reducing the burden of cardiovascular disease at population level. Aim : The objective of the study was to assess the cardiovascular health from a forward-looking perspective on health responsibility in order to improve attitudes approaches. Materials and methods : The study is a cross-sectional community survey with multistage sampling. A validated questionnaire was used and filled up by the participating physicians. Cardiovascular health was measured using the cardiovascular health metrics categories according the definition of the American Heart Association. Results : A total of 2,612 respondents (mean age 56.83±13.8 years, range 18 to 92 years, 34.8% male) were included into the study. The scores of cardiovascular health and its subscales of participants free of cardiovascular disease were found to be significantly higher ( p <0.001), with the exception of health behaviours subscale scores ( p =0.922). However, health behaviour subscale scores for personal attitudes approaches towards responsibility for health were found to be significantly higher in comparison to social ( p <0.001) and undecided approaches ( p <0.001). Conclusions : Our data suggest that a population free of cardiovascular disease is not likely to engage in health behaviours to prevent the onset of the disease, appearing willing to improve their behaviours after acquiring the disease. Further studies are needed to account for the efficacy interventions focusing on individual’s motivation to assume personal responsibility for behaviours affecting their health.